The antecedents of fear of violent crime in Selangor, Malaysia / Mohd Ramlan Mohd Arshad, Nurul Nadia Abu Hassan and Zaliha Hj Hussin - Mohd Arshad, Mohd Ramlan; Abu Hassan, Nurul Nadia; Hussin (Hj.), Zaliha (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
The aim of this paper is to study on the factors toward fear of violent crime. The respondents for this study are whom involved as community police in their residential area. The main objective of the research is to investigate the relationship between perceived risk of victimization, media effects and lack of trust and confident toward police with the community fear on crime. The statistical result shown that perceived risk victimization has strongest relationship with fear of crime (r=.892, p<.005).Hence, the Royal Malaysia Police must ensure they run the security task effectively to ensure community hold the trust and confidence on them in ensuring harmonious environment preserved.